Genetic and mechanistic basis for APOBEC3H alternative splicing, retrovirus restriction, and counteraction by HIV-1 protease - Diako Ebrahimi (Nature Portfolio, 2018)
Human APOBEC3H has several haplotypes and splice variants with distinct anti-HIV-1 activities, but the genetics underlying the expression of these variants are unclear. Here, the authors identify an intronic deletion in A3H haplotype II resulting in production of the most active splice variant, which is counteracted by HIV-1 protease.